Disrupting the Archives and Loosening the Evangeline Knot: Finding an Undercurrent in Antoine-J. Léger’s Elle et lui and Une fleur d’Acadie - Thomas, Leanna (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2021)
For marginalized francophone communities who left little written record in the colonialarchives, 20th-century literature confronts absences and silences resulting from imperialarchival dominance and popular narratives. This article mobilizes Acadian author Antoine-J.Léger’s novels Elle et lui : tragique idylle du peuple acadien (1940) and Une fleur d’Acadie :un épisode du grand dérangement (1946) to consider how Acadian writers began challengingthe stability of archival records and subverting the dominance of the version of eventsimagined by Henry Wadsworth Longfellow in his poem Evangeline: A Tale of Acadie (1847).